Check-list of Pteridophytes from Gujarat State, Western India - Rajput, Kishore S.; Kachhiyapatel, Ronak N.; Patil, Sachin M.; Vasava, Ajit M.; Patel, Ravi S.; Patel, Suresh K.; Raole, Vinay M. (Phytotaxa, 2021)
Gujarat is the westernmost state of India and is known for varied climatic conditions starting from moist deciduous forest to pure desert conditions as in the Greater Rann of Kachchh. A major part of the geographical area of Gujarat is a semi-arid region with dry climatic conditions; but studies on pteridophyte diversity of Gujarat state have always been neglected by botanists. Consequently, the diversity of pteridophytes in the state was poorly represented with 12 genera and only 16 species reported in previous literature. The present investigation was carried out to document species diversity and to update the checklist of pteridophytes occurring in Gujarat state. A total of 50 naturally occurring species or subspecies representing 23 genera in 14 families were collected from different regions of the state. An additional 13 species cultivated in the University Botanical Garden or in homes and gardens have also been noted. Among the indigenous species, Aleuritopteris anceps, A. formosana, Ceratopteris thalictroides subsp. thalictroides, Ophioglossum indicum, O. lancifolium, O. lusoafricanum and O. petiolatum are reported as new distributional records for the state. The maximum diversity was observed in south Gujarat, followed by Central Gujarat and the Saurashtra region whereas less diversity was observed in the North and Kachchh regions. Results of our study are compared to findings made by earlier workers.